A Geomorphological Aproch to an integrated survey of part of calabria - Daniel, J.A.R.K. (My University, 1970)
The object of this i n t e g r a t e d survey wr.s to apply goomorphol o g i c a l techniques, to i n v e s t i g a t e and evaluate the natural resources of a developing area. Therefore quite appropri tely Northern C a l i b r i a i n Southern I t a l y was selected for such a survey to be c r r i e d out. This project was completed i n three stages. F i r s t the a e r i al photographs were examined to o b t a i n preliminary information of the t e r r a i n . In the second stage, the f i e l d i n f o r ution on form, s o i l, l i t h o l o y , hydrological conditions and /egetation of the t e r r a in was c o l l e c t e d on a team b a s i s . The f i n a l stage of the project was to present a t h e s i s b?;sed on the information c o l l e c t e d both i n the f i e l d and i n the laboratory. This thesis i s d i v i d e d i n t o two parts. Part one i s composed of, chapters on geonorphology, iithology, s o i l and land use of the general area of survey, which includes the whole of Northern Calabri It also includes a chapter on the techniques used i n this : r e j e c t . In the l a s t chapter of t h i s part the use of georiorpholcy i n an integrated survey i s diecussed. The second part of t h i s thesis i s concerned with a small area i n Calabria, namely ilan Farco Argentano last. Here too the chapters on geomor:hology, l i t h o l o y , s o i l and land use of this area are included. Apart from t h i s general information, a s p e c i f i c problem Of t h i s area was tackled) Mass movements and slopes. The l a st chapter deals with the use of geomorphological approach to a s p e c i f i c problem. Therefore the use of geomorphological techniques in a general survey and a s p e c i f i c purpose survey i s evaluated in t h i s thecis.